Adiwiyata School Management In Improving Brand Image In Madrasah - Afla, Nurul; Sugiarto, Lilik (Development: Studies in Educational Management and Leadership, 2024)
This study examines the management strategies employed by Adiwiyata schools and their impact on enhancing the brand image of madrasahs. Utilizing a qualitative research design, the investigation incorporates observations, semi-structured interviews, and document analysis to derive insights. The findings indicate that effective management is pivotal in establishing a positive brand identity for madrasahs.  Key results suggest that successful brand development is contingent upon strategic initiatives that prioritize high-quality educational processes and an environmentally sustainable curriculum aligned with the Adiwiyata program. Such a curriculum not only elevates educational standards but also fosters environmental stewardship, thereby enhancing institutional reputation and societal impact.  The study emphasizes the necessity of integrating effective management practices with sustainable educational initiatives to strengthen the perceived value of madrasahs. Recommendations for practice focus on the continuous improvement of pedagogical methods and curriculum development, highlighting the critical interplay between quality education and environmental sustainability in enhancing the brand image of madrasah